Rapid Immunocapture of Pseudomonas putida Cells from Lake Water by Using Bacterial Flagella - Morgan, J. Alun W. (1991)
Monoclonal antibodies to Pseudomonas putida Paw340 cells were produced. In an enzyme-linked immunosorbent assay (ELISA) against whole bacterial cells, a hybridoma cell line termed MLV1 produced a monoclonal antibody that reacted with P. putida Paw340 but showed no cross-reaction with 100 medical isolates and 150 aquatic isolates. By ELISA, immunogold electron microscopy, and Western blot (immunoblot) analysis, MLV1 antibody was found to react with purified bacterial flagella. The surfaces of magnetic polystyrene beads were coated with MLV1 antibody. By mixing MLV1 antibody-coated beads with lake water samples containing the target P. putida host, bead-cell complexes which could be recovered by attraction towards a magnet were formed. Prevention of nonspecific attachment of cells to the beads required the incorporation of detergents in the isolation protocol. These detergents affected colony-forming ability; however, the cells remained intact for direct detection. When reisolated by standard cultural methods, approximately 20% of the initial target population was recovered. Since the beads and bead-cell complexes were recovered in a magnetic field, target bacteria were separated from other lake water organisms and from particulate material which was not attracted towards the magnet and were thereby enriched. This method may now provide a useful system for recovering recombinant bacteria selectively from environmental samples.